The Lactate Minimum Test: Concept, Methodological Aspects and Insights for Future Investigations in Human and Animal Models - Messias, Leonardo H. D.; Gobatto, Claudio A.; Beck, Wladimir R.; Manchado-Gobatto, Fúlvia B. (Frontiers in Physiology, 2017)
In 1993, Uwe Tegtbur proposed a useful physiological protocol named the lactate minimum test (LMT). This test consists of three distinct phases. Firstly, subjects must perform high intensity efforts to induce hyperlactatemia (phase 1). Subsequently, 8 min of recovery are allowed for transposition of lactate from myocytes (for instance) to the bloodstream (phase 2). Right after the recovery, subjects are submitted to an incremental test until exhaustion (phase 3). The blood lactate concentration is expected to fall during the first stages of the incremental test and as the intensity increases in subsequent stages, to rise again forming a “U” shaped blood lactate kinetic. The minimum point of this curve, named the lactate minimum intensity (LMI), provides an estimation of the intensity that represents the balance between the appearance and clearance of arterial blood lactate, known as the maximal lactate steady state intensity (iMLSS). Furthermore, in addition to the iMLSS estimation, studies have also determined anaerobic parameters (e.g. peak, mean and minimum force/power) during phase 1 and also the maximum oxygen consumption in phase 3; therefore, the LMT is considered a robust physiological protocol. Although encouraging reports have been published in both human and animal models, there are still some controversies regarding three main factors: 1) the influence of methodological aspects on the LMT parameters; 2) LMT effectiveness for monitoring training effects; and 3) the LMI as a valid iMLSS estimator. Therefore, the aim of this review is to provide a balanced discussion between scientific evidence of the aforementioned issues, and insights for future investigations are suggested. In summary, further analyses in necessary to determine whether these factors are worthy, since the LMT is relevant in several contexts of health sciences.